An urban governance approach in the development of commercial brownfield: A case study of Iskandar Malaysia (International Journal of Built Environment and Sustainability, 2019)
Brownfield development has become one of the sectors to be emphasised imperatively due to emerging greenfield scarcity throughout Malaysia. A brownfield site may have real or perceived contamination issues that require intervention to revive for beneficial use. As of to-date, there is still a number of brownfield sites in Iskandar Malaysia, albeit brownfield revival projects, via planning and policy measures, have been carried out over the years. In this light, a mode of governance is suggested to be a significant factor in the stagnation and success of brownfield development. Therefore, this paper aims to revisit the urban governance modes of brownfield development in Iskandar Malaysia, with a focus on commercial brownfield development. Specifically, two objectives are highlighted in this paper: (i) to assess the site-level success of completed brownfield developments, namely the Paradigm Mall, Skudai and the Danga City Mall, Johor Bahru; and based on the assessment outcomes, it is then (ii) to identify an efficient and suitable mode of governance for commercial use brownfield development. A measuring tool and an indexing scheme to screen brownfield sites were employed alternately. Results show that the Paradigm Mall achieved a higher site-level success compared to the Danga City Mall. Under this light, compared to the corporatist mode of governance, the clientelistic mode of governance with a material objective is highly in relation to a better success of commercial use brownfield development in the background of Iskandar Malaysia. These findings offer valuable messages and insights to practitioners, particularly local policy-makers, that an often-neglected governance mode approach is essential in determining the brownfield development outcome.
Keywords: Urban Governance Mode; Brownfield Development; Site-level Success; Commercial; Iskandar Malaysia